Gender and Occupation: Automatic Cognition Test - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. This tool, Gender and Occupation: Automatic Cognition Test, captures ‘automatic cognition’ (i.e., cognition that is fast, effortless, and occurs with little conscious awareness) regarding the gendered nature of specific activities and occupations. An increasing number of policy interventions aim to change gender norms and biased attitudes against women, including those regarding which occupations it is appropriate for women to work in. However, such implicit attitudes and biases are notoriously prone to measurement error. Rather than the more complex Implicit Association Test (IAT), this tool captures automatic cognition based on the simpler Affect Misattribution Procedure (Miles et al. 2019). This tool can be used to diagnose the strength of automatic cognitive processes regarding gender and occupations in a given population, but also to assess the impact of interventions aiming to shift attitudes or norms. Users may want to use this tool alongside other measures of gender attitudes, as well as the respondent’s current occupation. This data study includes following files. 1. A survey document (including implementation guidelines). 2. Two files, CAPI_Choices and CAPI_Survey, along with the accompanying files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with others, for constructing a CAPI program ready for survey implementation.